InN quantum dots on GaN nanowires grown by MOVPE. Issue 3 (17th February 2014) - Bi, Zhaoxia; Lindgren, David; Johansson, B. Jonas; Ek, Martin; Wallenberg, L. Reine; Gustafsson, Anders; Borgström, Magnus T; Ohlsson, Jonas; Monemar, Bo; Samuelson, Lars
Abstract: In this work, growth of InN quantum dots (QDs) on GaN nanowires (NWs) by metal‐organic vapour phase epitaxy is demonstrated, illustrating the feasibility to combine 0D and 1D structures for nitride semiconductors. Selective area growth was used to generate arrays of c‐oriented GaN NWs using Si3 N4 as the mask material. In general, InN QDs tend to form at the NW edges between the m‐plane side facets, but the QD growth can also be tuned to the side facets by controlling the growth temperature and the growth rate. TEM characterization reveals that I1 ‐type stacking faults are formed in the QDs and originate from the misfit dislocations at the InN/GaN interface. Photoluminescence measurement at 4 K shows that the peak shifts to high energy with reduced dot size. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)